Sosialisasi Sport Massage pada Guru PJOK di Yayasan Ponpes Nurul Iman Ujan Rintis Kabupaten Lombok Tengah - Herlina, Herlina; Burhan, Zakir; M. Rifai, Agus Sari; Nurhidayati, Desy (Yayasan Arfah Bin Haji Muhammad Saleh, 2025)
The lack of competence among Physical Education (PE) teachers in Central Lombok Regency in applying sports massage, as well as the limited use of manipulation techniques in sports learning, has become an obstacle to the development of students’ physical skills and well-being. This community service program aims to improve PE teachers’ understanding and skills in sports massage through comprehensive training. The methods used in this activity are lecture and demonstration/practice methods. The activity was attended by 25 junior high school PE teachers from East Kutai Regency. Evaluation results showed that 92.8% of participants had mastered the sports massage material, while 86.3% were able to apply the techniques effectively. It is expected that this training will enhance the competence of PE teachers in integrating sports massage into sports learning, thereby having a positive impact on physical recovery, athletic performance, and student well-being at the Nurul Iman Islamic Boarding School Foundation, Ujan Rintis, Central Lombok Regency.